On computing Hilbert bases via the Elliot–MacMahon algorithm - Pasechnik, Dmitrii V. (2012)
The ways of using the Elliot–MacMahon algorithm to compute the Hilbert base of a system of linear Diophantine equations known so far are either not efficient or can fail to terminate. We present a version of an algorithm exploiting this range of ideas, which however is reasonably efficient as well as finite.